Analisis Keamanan Cloud Dengan Zero Trust Dan Blockchain Yang Tangguh - Fitrian, Harry Pribadi; Neni, Neni; Aziz Bisri, Farhan Nur; Al Fathir, Muhammad Willy; Hizbulloh, Muhammad Jaisy (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This study integrates Zero Trust Architecture (ZTA) and Blockchain to strengthen cloud computing security. In the digital era, cloud computing has become a mainstream technology for data storage and processing globally. However, traditional perimeter-based security models have proven ineffective in dealing with modern threats, such as insider threats increasing by 60% and ransomware attacks on major cloud computing providers in 2022 resulting in billions of dollars in losses, highlighting the weaknesses of existing security models. Zero Trust Architecture (ZTA) offers a solution with a granular access control approach and layered authentication, but its implementation still faces challenges in efficiency and scalability, Blockchain, with its decentralized technology and immutable records, improves data transparency and integrity, but its use is often constrained by high energy consumption and latency. This study aims to explore between ZTA and Blockchain as innovative solutions to improve cloud security. By combining ZTA-based access control and Blockchain transparency, this study develops a security model that is resilient to both internal and external threats. Simulations show that ZTA and Blockchain integrity can reduce insider threats by 35% and increase data audit efficiency by 20%. This approach not only offers stronger protection but also provides an adaptive and transparent system for rapidly evolving cloud infrastructure.